“Você me paga, bandido!”:: Cruzamentos dialógicos entre narrativa literária e judicial de violência doméstica - Freitas, Lúcia Gonçalves de; Curado, Maria Eugênia (Language and Law / Linguagem e Direito, 2022)
This article explores parallels between literary narratives and judicial narratives about domestic violence, based on the Bakhtinian dialogic concept of language. The article takes the short story “Você me paga, bandido!” by Dalton Trevisan and compares and contrasts it with narrative excerpts from judgments of the Superior Court of Justice concerned with the 'Maria da Penha' Law. This discursive-literary approach discusses gender issues that permeate domestic violence in Brazil and its treatment by the legal system after the advent of this law. The analyses explore more recurrent dialogical links that permeate the narratives, such as guilt mitigation, power games, notions of jealousy, honor, drunkenness, male dignity, female resistance and the trivialization of violence. We believe that the discursive-literary approach developed here can support interdisciplinary action both in the penal treatment of domestic violence, and in its prevention through educational measures.